Determination of safety margins for whole blood concentrations of alcohol and nineteen drugs in driving under the influence cases. (February 2016) - Kristoffersen, Lena; Strand, Dag Helge; Liane, Veronica Horpestad; Vindenes, Vigdis; Tvete, Ingunn Fride; Aldrin, Magne
Highlights: Safety margins for whole blood concentrations of alcohol and nineteen drugs. Bayesian model to estimate the errors standard batch, work list and replicate. The safety margins for alcohol varied between 10.4% (0.1‰) to 4.0% (4.0‰). The safety margins for DUI related drugs were 25–41% at a 99% safety level. Road Traffic Act, per se limits and limits for graded sanctions. Abstract: Legislative limits for driving under the influence of 20 non-alcohol drugs were introduced in Norway in February 2012. Per se limits corresponding to blood alcohol concentrations (BAC) of 0.2 g/kg were established for 20 psychoactive drugs, and limits for graded sanctions corresponding to BACs of 0.5 and 1.2 g/kg were determined for 13 of these drugs. This new legislation made it possible for the courts to make sentences based on the analytical results, similar to the situation for alcohol. To ensure that the reported concentration is as least as high as the true concentration, with a 99% safety level, safety margins had to be calculated for each of the substances. Diazepam, tetrahydrocannabinol (THC) and alcohol were used as model substances to establish a new model for estimating the safety margins. The model was compared with a previous used model established several years ago, by a similar yet much simpler model, and they were found to be in agreement. The measurement uncertainties depend on the standard batch used, the work list and the measurements' replicate. A Bayesian modelling approach was used to determine the parameters in the model, using a dataset of 4700 diazepam positive specimens and 5400 THC positive specimens. Different safety margins were considered for low and high concentration levels of diazepam (≤2 μM (0.6 mg/L) and >2 μM) and THC (≤0.01 μM (0.003 mg/L) and >0.01 μM). The safety margins were for diazepam 19.5% (≤2 μM) and 34% (>2 μM), for THC 19.5% (≤0.01 μM) and 24.9% (>0.01 μM). Concentration dependent safety margins for BAC were based on a dataset of 29 500 alcohol positive specimens, and were in the range 10.4% (0.1 g/kg) to 4.0% (4.0 g/kg) at a 99% safety level. A simplified approach was used to establish safety margins for the compounds amphetamine, MDMA, methamphetamine, alprazolam, phenazepam, flunitrazepam, clonazepam, nitrazepam, oxazepam, buprenorphine, GHB, methadone, ketamine, cocaine, morphine, zolpidem and zopiclone. The safety margins for these drugs were in the range 34–41%.